The Role of Motivation, Work Discipline and Training in Improving Employee Performance - Tri Ariprabowo; Dini Marita Sari; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2021)
his study aims to test the effect of motivation, work discipline and motivation on employee performance. The number of samples in this study were 89 operational employees at PT. Generation of Java-Bali UP Gresik, using the technique method Probability Sampling of Random Sampling type. Data collection in this study was using questionnaires and interviews. The data analysis technique used is multiple linear regression analysis. The results of this study conclude that the results of simultaneous testing of motivation, work discipline and training have a significant effect on performance. Partial test results Motivation has an effect and is significant on performance, work discipline also has an effect and is significant on performance and training also has an effect and is significant on performance